Asking ethical questions in northern First Nations housing research: A relational approach - Dextrase, Hillary; McCartney, Shelagh; Herskovits, Jeffrey; Solokov, Sean (Canadian Planning and Policy / Aménagement et politique au Canada, 2026)
Northern First Nations housing has been shaped by a history of colonial exploitation and a state of continuous crisis. Where external housing solutions have failed, many Indigenous communities are building a self-determined reimagination of housing and home. Researchers are often invited to support this work, and through participatory research methods, can work together with communities to influence policy, program and systems change. However, engaging northern First Nations in research in the colonial context comes with numerous ethical considerations which often extend beyond the scope of institutional research ethics review. Grounded in a decade of planning and policy research experience engaging the voices of northern First Nations, this article offers reflections on critical ethical questions about research in this context. Exploring the complexities of balancing the ethical requirements of institutions with those set out by context and relationships, this article provides insight into the importance of relational ethical practice when engaged in planning and policy research with northern First Nations.